Highly Regioselective Synthesis of Pyrazole Derivatives Using a 1,3-Dipolar Cycloaddition Approach - Alizadeh, Abdolali; Moafi, Leila; Zhu, Long-Guan (Synlett, 2016)
We report a simple and regioselective procedure for the synthesis of 1H-pyrazol-5-yl (2-hydroxyphenyl)methanone derivatives. This process includes the 1,3-dipolar cycloaddition reaction of nitrile imines generated in situ from hydrazonoyl chloride and triethylamine with 3-formylchromones.
Keywords: 3-formylchromone; pyrazole; hydrazonoyl chloride; nitrile imine; 1,3-dipolar cycloaddition